Transformasi Gen SoSPS1 Melalui Agrobacterium tumefaciens pada Tanaman Anggur Bali (Vitis vinifera L. var. Alphonso Lavalle) Secara In Planta - I GUSTI AGUNG INDRA MERTAWAN; RINDANG DWIYANI; HESTIN YUSWANTI (Agrotrop : Journal on Agriculture Science, 2018)
In Planta Transformation of SoSPS1 Gene Through Agrobacterium tumefaciens in Balinese Grapevine (Vitis Vinifera L. var. Alphonso Lavalle). Vitis vinifera L. var. Alphonso Lavalle is one of the cultivar of grapevine cultivated in Bali. The sour taste of fruit is one of the problem of these cultivar that make it is less prefer by consumer. Research regarding improvement of fruit quality through genetic engineering has been investigated. The aims of the research were to find out the most proper methods of in planta transformation mediated with Agrobacterium tumefaciens applied on V. vinifera. The T-DNA harbored the SoSPS1 gene under the control of promoter of the CaMV from Cauliflower Mosaic Virus and contained the NPTII gene, a kanamycin resistant gene as a selectable marker for transformant selection. V. vinifera seedlings from stem cutting aged 40-50 days were ripped and then dipped with the bacterial suspension for 1 hour, 2 hours, 1 day, and 2 days. Visualization of V. vinifera samples after PCR showed that ripping and dipping for 2 hours method was positively integrated with NPTII gene. The dipping of plants wound for 2 hours treatment was effective for inserting gene of interest in ripping and dipping methods.